2011
DOI: 10.5334/ijic.674
|View full text |Cite
|
Sign up to set email alerts
|

Impact on continuity of care of decentralized versus partly centralized mental health care in Northern Norway

Abstract: BackgroundThe issue of continuity of care is central in contemporary psychiatric services research. In Norway, inpatient admissions are mainly to take place locally, in a system of small bed-units that represent an alternative to traditional central psychiatric hospitals. This type of organization may be advantageous for accessibility and cooperation, but has been given little scientific attention.AimsTo study whether inpatients’ utilization of outpatient services differ between an area with a decentralized ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…Previously Myklebust et al [40] reported that in Norway outpatient and day-hospital services may be filters in the pathway to inpatient care. They underlined that this depends on the structure of the whole service system, since decentralized psychiatric beds may hinder the development of various local psychiatric services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously Myklebust et al [40] reported that in Norway outpatient and day-hospital services may be filters in the pathway to inpatient care. They underlined that this depends on the structure of the whole service system, since decentralized psychiatric beds may hinder the development of various local psychiatric services.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the structural deinstitutionalization of mental health care, there has been a call for greater service coordination between inpatient and outpatient services [40]. Intensive case management can reduce the provision of hospitalization if the hospitalization level is high, but the effect is limited if inpatient treatment is already at a low level [7].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, nine of the studies were at high risk of selection bias [2,1,14,[20][21][22]27,30,29,31,36] due to uncontrolled confounders or, for before and after studies, due to having no control group for comparison. All studies were also unclear [20,30,29,31,40] or at high risk [2,1,14,16,19,21,22,26,27,[36][37][38] of performance bias due to an imbalance in treatment intensity or the existence of additional co-occurring interventions -such as one treatment group receiving extended 24-hour-care, assertive engagement, or home treatment whilst the other does not. Design specific issues, such as having only one site per intervention group in cluster-level studies or a lack of an appropriate concurrent control altogether, means all the studies were also at high risk of other potential sources of bias.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…Such organizational varieties may have implications for patients’ patterns of care, and we have earlier studied how the general structure of mental health systems may affect various outcomes such as coercion, continuity of care, and utilization of beds. 4 , 16 19 …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, 70% of the total inpatient stays in Vesterålen are at the local community level at the DPC; only about 30% are referred further to the CMH. 16 19 …”
Section: Introductionmentioning
confidence: 99%